If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -5y + -9 = -1y + 1 Reorder the terms: -9 + -5y = -1y + 1 Reorder the terms: -9 + -5y = 1 + -1y Solving -9 + -5y = 1 + -1y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add 'y' to each side of the equation. -9 + -5y + y = 1 + -1y + y Combine like terms: -5y + y = -4y -9 + -4y = 1 + -1y + y Combine like terms: -1y + y = 0 -9 + -4y = 1 + 0 -9 + -4y = 1 Add '9' to each side of the equation. -9 + 9 + -4y = 1 + 9 Combine like terms: -9 + 9 = 0 0 + -4y = 1 + 9 -4y = 1 + 9 Combine like terms: 1 + 9 = 10 -4y = 10 Divide each side by '-4'. y = -2.5 Simplifying y = -2.5
| 6(c+4c)=4c-18 | | 6x+4(4x-15)=50 | | -2=w/5 | | 3k-9=7+2k-k | | -4x+4(2x+8)=-8+8(x+8) | | L+50=1.32 | | -8/9(9+y)=64 | | 5/3x+1/3x=8/3+8/3x | | -8(t-7)-7(2t+1)=-17 | | 7(x-4)=6(x+1)-3 | | 5(40-(40-x))+10(40-x)+25x=405 | | -59=-5(4a-4)+1 | | -x-(13+4x)=-3(5-9k)+2 | | -0.8(2x-6)=1.7(3-x) | | 3y+(-11y)= | | 12x^2-81x-3/7=0 | | x/3-9=11 | | 12x^2-81x-3/7 | | -15t-9+8t=4t-3 | | 4+-1x=-1x+4 | | 0.5x-0.1=0.4-0.6(9-2x) | | 3y-7=2y+5 | | 3-6x=-80-5x | | 4+-1x=1x+4 | | x^2+1x=272 | | -2y+8=3y+28 | | 6x^24= | | 3x+1.5x+x+180=455 | | 6(4x-3)-10= | | 7x+9x-69=46-7x | | 2(9x-1)=99-7(3-4k) | | 8n-3.5=-20 |